2009
DOI: 10.1002/lsm.20765
|View full text |Cite
|
Sign up to set email alerts
|

Toluidine blue O photodynamic inactivation on multidrug‐resistant pseudomonas aeruginosa

Abstract: MDR did not affect the susceptibility of P. aeruginosa strains to TBO-PDI. The efflux pump played an insignificant role in TBO-PDI of MDR P. aeruginosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…Several studies have shown that multiresistant microorganisms can be just as susceptible to PDT as similar non-multiresistant strains [34]. However, according to Tegos and Hambin [35] and George et al [36], multiresistant strains can be more difficult to eradicate with PDT compared to antibiotic-susceptible strains.…”
Section: Regardlessmentioning
confidence: 98%
“…Several studies have shown that multiresistant microorganisms can be just as susceptible to PDT as similar non-multiresistant strains [34]. However, according to Tegos and Hambin [35] and George et al [36], multiresistant strains can be more difficult to eradicate with PDT compared to antibiotic-susceptible strains.…”
Section: Regardlessmentioning
confidence: 98%
“…A substantial number of studies state that the photodynamic approach can also be used to kill microorganisms, and is considered a promising alternative to treating oral biofilms involved in several major oral diseases such as candidiasis [11,12], dental caries [13], and periodontal disease [14]. In recent years, PACT/PDI has been proposed as an alternative treatment for localized bacterial infections [15].…”
Section: Photodynamic Antimicrobial Chemotherapy In Dentistrymentioning
confidence: 99%
“…A PACT/PDI/PDT regimen can be beneficial for the elimination of microorganisms during systematic therapies of biofilm-dependent diseases, and is able to inactivate some of the known antibiotic-resistant microbial pathogens [15]. Therefore, this approach would be beneficial for the treatment of biofilm-dependent oral diseases, considering the high accumulation of bacteria in the oral environment and the easy access to the site of the disease.…”
Section: Photodynamic Antimicrobial Chemotherapy In Dentistrymentioning
confidence: 99%
“…55,56 In a model study, it was demonstrated that 60 MDR Pseudomonas aeruginosa isolates could be killed (up to 6-7 log 10 reduction in viable cell counts) using TBO-PDT. 57 This study also demonstrates that antibiotic-resistant P. aeruginosa was just as susceptible to PDI as antibiotic-susceptible strains. Another report demonstrated that PDI with cationic phthalocyanines has a substantial phototoxic effect in MDR strains of Aeromonas hydrophila.…”
Section: Pdi and Multidrug Effluxmentioning
confidence: 57%